Trauma Epidemiology Among Rescued Elderly Clients in Pre-Hospital Emergency Department of Mazandaran - Zoya Hadinejad; Hassan Talebi; Farhad Masdari (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives The aging population is increasing worldwide, and Iran is not an exception. Trauma is the fifth leading cause of death in patients over 65 years, and 28% of these people die as a result of trauma. Therefore, this study aimed to determine the incidence pattern of trauma in 60 years old and older cases divided by age and gender in order to develop strategies to prevent injuries in this high-risk age group. Methods & Materials In this cross-sectional retrospective study, the data of all the 60 years old and older cases admitted in the pre-hospital emergency system of Mazandaran were extracted during the five years (2010-2014). The data included age, sex, pre-hospital diagnosis, date, type of trauma, mechanism of trauma, location of accident, the victim’s status (driver, passenger, pedestrian or other), severity of injury, and season and time of the incident. The obtained data were analyzed using SPSS software version 19, chi-square and Fisher’s exact tests. Results The incidence of trauma in 2014 had a 1.7% increase compared to that in 2010. A total of 6844 cases (62.8%) surveyed were male, and 4054 cases (37.2%) were female. Most of the trauma cases occurred in the age group of 60-64 years with 3680 cases (33.8%). Most trauma cases in the elderly were related to traffic accidents with 6521 cases (59.8%), followed by falls, injuries and assaults with 3494(32%), 517(4.7%). and 257(4.2%) cases, respectively. Most trauma cases occurred in summer with 2982 cases (27.4%), and trauma was most likely to occur between 8 am to 12 pm with 3119(28.6%) cases. According to the Pearson’s chi-square test, there was a statistically significant relationship between the time of accident and the final status (P<0.05). The highest incidence of death was in the age group 60 to 64 years. Chance of survival was lower in men than in women. Conclusion The elderly are more prone to accidents due to physical changes caused by aging and inappropriate environmental conditions. According to the findings of the present study, accidents and falls are the most common cases of incidents in the elderly people. The risk of injury and disability in this age group can be prevented by comprehensive preventive and controlling programs.